2012
DOI: 10.3310/hta16090
|View full text |Cite
|
Sign up to set email alerts
|

The UK EndoVascular Aneurysm Repair (EVAR) trials: randomised trials of EVAR versus standard therapy.

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
170
0
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(189 citation statements)
references
References 140 publications
(207 reference statements)
3
170
0
7
Order By: Relevance
“…65 As per NICE guidance, 66 we assumed that emergency EVAR operations are only being performed in a research environment and, so, we have only included costs for open emergency repair in our estimates. For emergency open repair an estimate of per patient costs was updated from the MASS trial, in the following way:…”
Section: Costs For Elective and Emergency Aneurysm Repairmentioning
confidence: 99%
“…65 As per NICE guidance, 66 we assumed that emergency EVAR operations are only being performed in a research environment and, so, we have only included costs for open emergency repair in our estimates. For emergency open repair an estimate of per patient costs was updated from the MASS trial, in the following way:…”
Section: Costs For Elective and Emergency Aneurysm Repairmentioning
confidence: 99%
“…EVAR is now the conventional management of aortic aneurysms with suitable anatomy [1]. This has been proven abundantly in registry and randomized trials, especially for infrarenal and descending thoracic aortic aneurysms.…”
Section: Case Reportmentioning
confidence: 99%
“…The study largely confirmed the results of the EVAR 1 trial and showed no significant differences regarding the all-cause mortality rate after the first postoperative year and in contrast to the EVAR 1 trial also showed no differences regarding the aneurysm-related mortality rate between the two treatment methods. Additional prospectively randomized multicenter studies include the OVER trial (Open Versus Endovascular Repair) [20] and the UK EVAR trial [21]. These also showed an early survival advantage for endovascular repair but the all-cause mortality rate could not be significantly improved by EVAR.…”
mentioning
confidence: 99%